The secretion pattern of perivascular fat cells is different from that of subcutaneous and visceral fat cells - Rittig, K.; Dolderer, J. H.; Balletshofer, B.; MacHann, J.; Schick, F.; Meile, T.; Küper, M.; Stock, U. A.; Staiger, H.; MacHicao, F.; Schaller, H. E.; Königsrainer, A.; et al. (Diabetologia, 2012)
Aims/hypothesis We have previously found that the mass of perivascular adipose tissue (PVAT) correlates negatively with insulin sensitivity and post-ischaemic increase in blood flow. To understand how PVAT communicates with vascular vessels, interactions between perivascular, subcutaneous and visceral fat cells with endothelial cells (ECs) were examined with regard to inflammatory, metabolic and angiogenic proteins. To test for possible in vivo relevance of these findings, circulating levels of the predominant secretion product, hepatocyte growth factor (HGF), was measured in individuals carefully phenotyped for fat distribution patterns. Methods Mono-and co-cultures of human primary fat cells with ECs were performed. mRNA expression and rotein production were studied using Luminex, cytokine array, RealTime Ready and ELISA systems. Effects of HGF on vascular cells were determined by WST assays. In patients, HGF levels were measured by ELISA, and the mass of different fat compartments was determined by whole-body MRI. Results In contrast with other fat cell types, PVAT cells released higher amounts of angiogenic factors, e.g. HGF, acidic fibroblast growth factor, thrombospondin-1, serpin-E1, monocyte chemotactic protein-1 and insulin-like growth factor-binding protein-3. Cocultures showed different expression profiles from monocultures, and mature adipocytes differed from pre-adipocytes. HGF was preferentially released by PVAT cells and stimulated EC growth and smooth muscle cell cytokine release. Finally, in 95 patients, only PVAT, not visceral or subcutaneous mass, correlated independently with serum HGF levels (p00.03; r00.225). Conclusions Perivascular (pre-)adipocytes differ substantially from other fat cells with regard to mRNA expression and protein production of angiogenic factors. This may contribute to fat tissue growth and atherosclerotic plaque complications. Higher levels of angiogenic factors, such as HGF, in patients with increased perivascular fat mass may have pathological relevance. © 2012 Springer-Verlag.
CRIS-Team Scopus Importer:2024-12-11
Keywords: Adipocytes; Angiogenic factors; Atherosclerotic plaque; HGF; Insulin sensitivity; Perivascular tissue; Pre-adipocytes